Investigate how construction waste generation rate is, different for every types of project in peninsular Malaysia, using site visit method - Subramaniam, Shivaraj; Abdullah, Abd Halid; Nagapan, Sasitharan; Kupusamy, Kumanan; Manian, Haritharan; Daud, Zawawi (Penerbit UTHM, 2018)
Malaysia is a rapid development of its urban centre, and where construction and demolition (C&D) waste generation is increasing proportionally with the new construction industry development. In Malaysia, the most crucial issue highlighted by local researchers is excessive of C&D waste generation. The transfer of construction and demolition waste at landfills has brought about major ecological concerns and government sources demonstrate that there is an intense lack of landfill space in Malaysia. The aim of this study is to investigate the construction waste generation rate in Malaysia due to different project types. To obtain the waste generation rate, construction sites visit is required. In construction site, direct and indirect approaches were utilized to collect C&D waste generation data based on data available. For the construction waste generation rate, nonresidential projects obtained smallest value such as 0.008 t/m2 while residential projects obtained highest value such as 0.016 t/m2. Social amenities obtained 0.010 t/m2 of waste generation rate. Waste generation rate is different compare to waste generation due to projects sizes. Waste generation rate shows the actual waste generation for every projects type based on gross floor area. The gross floor area is important parts need to be considered during waste generation which provide actual waste generation data. Waste generation rate plays an important role to measure waste generation for every type of projects. This study, will be very much beneficial for contractors and clients to control the construction waste in construction site and to identify efficiencies of projects using waste generation rate. Besides that, provide a generation rate on construction waste to the Government for control the waste and reduce illegal dumping in future.